2021
DOI: 10.3390/ijerph182010788
|View full text |Cite
|
Sign up to set email alerts
|

Processed and Unprocessed Red Meat Consumption and Risk for Type 2 Diabetes Mellitus: An Updated Meta-Analysis of Cohort Studies

Abstract: Type II diabetes mellitus (T2DM) is a metabolic disorder that occurs in the body because of decreased insulin activity and/or insulin secretion. The incidence of T2DM has rapidly increased over recent decades. The relation between consumption of different types of red meats and risk of T2DM remains uncertain. This meta-analysis was conducted to quantitatively assess the associations of processed red meat (PRM) and unprocessed red meat (URM) consumption with T2DM. We searched PubMed, Embase, Web of Science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Our findings on the association between IGT/diabetes and total meat and processed meat consumption are supported by previous observational studies [ 42 , 46 , 53 , 54 ]. A recent meta-analysis of cohort studies including over 680,000 participants reported findings in similar agreement with the current study, whereby compared to the lowest intake group, high consumption of processed red meat and unprocessed red meat increased T2D risk by 27% and 15%, respectively [ 54 ]. A prospective study conducted in French women found that those consuming a daily amount of processed meat (48g) had a significantly higher incidence of DM than women consuming 5 g of processed meat <1/week [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on the association between IGT/diabetes and total meat and processed meat consumption are supported by previous observational studies [ 42 , 46 , 53 , 54 ]. A recent meta-analysis of cohort studies including over 680,000 participants reported findings in similar agreement with the current study, whereby compared to the lowest intake group, high consumption of processed red meat and unprocessed red meat increased T2D risk by 27% and 15%, respectively [ 54 ]. A prospective study conducted in French women found that those consuming a daily amount of processed meat (48g) had a significantly higher incidence of DM than women consuming 5 g of processed meat <1/week [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Weight gain was highly correlated with increased energy intake in ultra-processed diet group increasing the risk of obesity and associated diseases including T2D [7]. On the contrary, an updated meta-analysis using US adults by Panet et al [44] and two other recent studies (9 year prospective cohort study on Chinees adults and a meta-analysis) [45,46], indicated that although the relative risk for T2D is less compared to processed meat, unprocessed red meat consumption still has a substantial risk of getting T2D [44][45][46]. Nevertheless, it is still unclear whether the later risk of T2D is solely related to meat consumption, or it is partly due to other dietary factors such as fat content, salt and total acid load coming from other foods consumed along with unprocessed meat that could contribute to T2D risk.…”
Section: Discussionmentioning
confidence: 99%
“…Meat consumption also provides 30–35% of the daily requirement for vitamin D and 21% for iron. Those are two out of five shortfall nutrients (vitamin D, calcium, potassium, iron, and fiber) in human diets that were indicated in the US Dietary Guidelines for Americans as posing a serious health concern for society [ 3 , 4 ]. Beef, pork, veal, and lamb also contain potassium, a third shortfall nutrient in the human diet, in amounts that qualify to label them with a “source of potassium” claim (at least 15% of the EU Nutrient Reference Value in 100 g of meat).…”
Section: Introductionmentioning
confidence: 99%